Evaluation of the usefulness of saliva for DNA methylation analysis in cohort studies. Issue 4 (8th August 2019) - Murata, Yui; Fujii, Ayaka; Kanata, Sho; Fujikawa, Shinya; Ikegame, Tempei; Nakachi, Yutaka; Zhao, Zhilei; Jinde, Seiichiro; Kasai, Kiyoto; Bundo, Miki; Iwamoto, Kazuya
Abstract: Introduction: Epigenetic information such as DNA methylation is a useful biomarker that reflects complex gene‐environmental interaction. Peripheral tissues such as blood and saliva are commonly collected as the source of genomic DNA in cohort studies. Epigenetic studies mainly use blood, while a few studies have addressed the epigenetic characteristics of saliva. Methods: The effects of methods for DNA extraction and purification from saliva on DNA methylation were surveyed using Illumina Infinium HumanMethylation450 BeadChip. Using 386 661 probes, DNA methylation differences between blood and saliva from 22 healthy volunteers, and their functional and structural characteristics were examined. CpG sites with DNA methylation levels showing large interindividual variations in blood were evaluated using saliva DNA methylation profiles. Results: Genomic DNA prepared by simplified protocol from saliva showed a similar quality DNA methylation profile to that derived from the manufacturer provided protocol. Consistent with previous studies, the DNA methylation profiles of blood and saliva showed high correlations. Blood showed 1, 514 hypomethylated and 2099 hypermethylated probes, suggesting source‐dependent DNA methylation patterns. CpG sites with large methylation difference between the two sources were underrepresented in the promoter regions and enriched within gene bodies. CpG sites with large interindividual methylation variations in blood also showed considerable variations in saliva. Conclusion: In addition to high correlation in DNA methylation profiles, CpG sites showing large interindividual DNA methylation differences were similar between blood and saliva, ensuring saliva could be a suitable alternative source for genomic DNA in cohort studies. Consideration of source‐dependent DNA methylation differences will, however, be necessary. Abstract : We compared quality of saliva methylome data collected by several DNA purification protocols and examined the characteristics of saliva methylome. Optimized protocol and identified characteristics such as common informative CpG sites to blood and unique epigenetic changes in saliva will contribute to promote the use of saliva for epigenetic studies in clinical settings and epidemiological cohort studies.